On a Problem of Z. Moszner - Faćziev, Valerić; Sahoo, Prasanna K. (Journal of Informatics and Mathematical Sciences, 2012)
In this note, we provide an answer to a problem of Z. Moszner regarding the stability of the additive Cauchy functional equation on semigroups.